Personality traits and vocational preferences of Junior High School students - CASTRO, MARIA JOANNA FRANCESCA (Archīum Ateneo, 2017)
This study utilized the Five Factor Theory of Personality Traits and the RIASEC Model of Vocational Preferences to understanding the personality traits and vocational preferences profile of 74 junior high school students in a private Catholic school. It also explored the relationship between personality traits and vocational preferences using the standardized instruments NEO-FF-I-3 and the VPI. Influence of personality traits on vocational preferences was also studied. The results of the study showed that the personality traits profile of junior high school students is generally average in terms of the five- factor inventory. Their vocational preferences profile is likewise generally average, except for Social preference which had a score of low. The study also revealed that the personality traits Neuroticism, Extraversion, and Openness to Experience correlate with the vocational preferences Investigative, Artistic, Social, and Enterprising. Moreover, results show that personality traits Neuroticism, Extraversion, and Openness to Experience are likely to influence the vocational preferences Realistic, Artistic, Social, and Enterprising. In conclusion, it was found that a relationship exists between Extraversion and Enterprising. Likewise, the relationship between Openness to Experience and Artistic is apparent. Furthermore, Neuroticism both correlates with and influences the vocational preference Social. Similarly, Openness to Experience also correlates with and influences the vocational preference Artistic. (206 words)